New endogenous herpesvirus of guinea pigs: biological and molecular characterization. - Bia, F J (1980)
Two known guinea pig herpesviruses, guinea pig cytomegalovirus (GPCMV) and guinea pig herpes-like virus (GPHLV), and well characterized. A third herpesvirus (GPXV) was originally isolated from leukocytes of healthy strain 2 guinea pigs. Growth of GPXV in guinea pig embryo fibroblastic cells produced a characteristic cytopathic effect. Electron microscopy of guinea pig cells infected with GPXV revealed the morphological development of a herpesvirus. Cross-neutralization tests and immunoferritin electron microscopy demonstrated that GPXV, GPCMV, and GPHLV were serologically distinct herpeviruses of guinea pigs. To confirm the distinction between these three herpesviruses, DNA genomes were compared by CsCl equilibrium buoyant density measurements and restriction endonuclease cleavage analysis. 32P-labeled viral DNA ws obtained from nucleocapsids isolated from virus-infected cells, and the buoyant density of GPXV DNA differed from that of GPCMV and GPHLV. Cleavage of viral DNAs with restriction endonucleases followed by gel electrophoresis revealed distinct patterns for each virus.